Estimating Tuberculosis Transmission Risks in a Primary Care Clinic in South Africa: Modeling of Environmental and Clinical Data. (18th January 2022) - Zürcher, Kathrin; Riou, Julien; Morrow, Carl; Ballif, Marie; Koch, Anastasia; Bertschinger, Simon; Warner, Digby F; Middelkoop, Keren; Wood, Robin; Egger, Matthias; Fenner, Lukas
Abstract: Background: Congregate settings, such as healthcare clinics, may play an essential role in Mycobacterium tuberculosis ( Mtb ) transmission. Using patient and environmental data, we studied transmission at a primary care clinic in South Africa. Methods: We collected patient movements, cough frequency, and clinical data, and measured indoor carbon dioxide (CO2 ) levels, relative humidity, and Mtb genomes in the air. We used negative binomial regression model to investigate associations. Results: We analyzed 978 unique patients who contributed 14 795 data points. The median patient age was 33 (interquartile range [IQR], 26–41) years, and 757 (77.4%) were female. Overall, median CO2 levels were 564 (IQR 495–646) parts per million and were highest in the morning. Median number of coughs per day was 466 (IQR, 368–503), and overall median Mtb DNA copies/μL/day was 4.2 (IQR, 1.2–9.5). We found an increased presence of Mtb DNA in the air of 32% (95% credible interval, 7%–63%) per 100 additional young adults (aged 15–29 years) and 1% (0–2%) more Mtb DNA per 10% increase of relative humidity. Estimated cumulative transmission risks for patients attending the clinic monthly for at least 1 hour range between 9% and 29%. Conclusions: We identified young adults and relative humidity as potentially important factors for transmission risks in healthcare clinics. Our approach should be used to detect transmission and evaluate infection control interventions. Abstract : By modeling epidemiological, clinical, and environmental data at a primary care clinic in South Africa, we identified young adults and relative humidity as potentially important factors for tuberculosis transmission. This approach should be used to estimate transmission and evaluate interventions.